ШЛЯХИ ВИКОРИСТАННЯ ФІНАНСОВИХ ІНСТРУМЕНТІВ ДЛЯ ЗАБЕЗПЕЧЕННЯ КЛІМАТИЧНОЇ БЕЗПЕКИ НА РЕГІОНАЛЬНОМУ ТА МІСЦЕВОМУ РІВНЯХ (International Journal of Innovative Technologies in Economy, 2018)
The paper discusses financial instruments that can be used to ensure climate security at the regional and local levels. The emphasis is on the application of the carbon tax, the "green" tariff, and the need to use, in addition to positive and negative financial instruments of the climate plan. The basic forms of climatic financial instruments at the regional and local levels are determined. The main measures to be taken to stop the ecological disaster in the Polissya regions of amber extraction are proposed, as well as the need to strengthen control and stimulate the financial interest of the regional communities in forest harvesting in their territory.